Social Life of The Samin Community, Bojonegoro Regency and the Potential as a Learning Source - Novi Triana Habsari; Suyahmo Suyahmo; Cahyo Budi Utomo; Gunawan Gunawan (Universitas Negeri Semarang, 2021)
Historically, the Samin community is a community that originated from the figure and thoughts of Samin Surosentiko with the surname Raden Kohar. The word Samin comes from the word sami - sami amin and stems from the anxiety of R. Surowijoyo who could not stand the cruelty of the Dutch colonial government against the people. He then made a moral move. Over time, the Samin community has experienced changes in their social life. This study aims to reveal the social life of the Samin community and the changes that occur in it. The method used in this research is descriptive qualitative. Data collection was done by interview, observation and documentation. The results of the study show that there are changes in the lives of the Samin people in Bojonegoro. This can be seen from the change in the mindset of the Samin community who are already aware of the importance of education. Many Samin people have received education up to the undergraduate level. Social changes that occur in the Samin community have the potential as a source of learning history, especially class X 2013 curriculum so that they can add insight into past lives so that they can be preserved.